Post-Conflict Justice And Sustainable Peace - Gates, Scott, 1957- 1957- (The World Bank, 2007)
No systematic study has examined the effect of post-conflict justice on the duration of peace on a global basis. This paper attempts to fill that void by building on a newly constructed dataset (Binningsbo, Elster, and Gates 2005), which reports the presence of various forms of post-conflict justice efforts (trials, purges, reparation to victims, and truth commissions) as well as processes associated with abstaining from post-conflict justice (amnesty and exile). It investigates the long-term effects of post-conflict justice on the duration of peace after conflict. It uses a Cox proportional hazard model to analyze the influence of the various types of post-conflict justice on the length of the peace period before the recurrence of violent conflict. Post-conflict trials as well as other types of justice do lead to a more durable peace in democratic as well as non-democratic societies, but the results are weak and are therefore difficult to generalize. Forms of non-retributive justice (that is, reparations to victims and truth commissions), however, are strongly associated with the duration of peace in democratic societies, but are not significant for non-democratic societies. Amnesty tends to be destabilizing and generally associated with shorter peace duration, but exile tends to lead to a more durable peace